Investigação dos aspectos neuropsicológicos do transtorno do espectro alcoólico fetal em uma amostra de crianças e adolescentes de São Paulo - Barrocas, Roberta Magalhães [UNIFESP] (2014)
Alcoholism is an important public health issue. Alcohol comsumption between expectant mothers in Brazil can be up to 55%, 6% of which displaying a drinking pattern compatible with alcoholism. Prenatal alcohol exposure may cause a range of physical, cognitive and behavioral effects known as Fetal Alcohol Spectrum Disorders (FASD). Neuropsychological outcome displayed by children and adolescentes with FASD can be widely variable considering that which diagnosed subject has been exposed to a unique pattern of maternal alcohol consumption and postnatal experiences regarding education, home environment and socioeconomic factors. Understanding the neuropsychological profile of pacients with FASD can help elucidate the teratogenic effects of alcohol exposure and its impact on brain and behavior and may contribute to the broadening of diagnostic criteria for FASD. The aim of this study was to investigate evidences of a neurobehavioral phenotype in multiple cases of brazilian children and adolescents diagnosed with FASD by describing and analysing the influence of clinical and environmental variables on pacient cognitive and behavioral functioning. Subjects and their parents responded to a customized neuropsychological test battery. Eighteen children between 4 and 6 years of age were assessed, from which 8 were girls. Most subjects lived with adoptive parentes, went to regular school and were diagnosed with Fetal Alcohol Syndrome (FAS) or Partial FAS. Almost half of them had intellectual disabilities. The neuropsychological functioning of the group as a whole involved attentional, verbal working memory and verbal fluency deficits. Verbal abilities and nonverbal fluency were found to be relatively preserved. No prevalence of distinctive behavioral problems was reported. FASD is a disorder characterized by intense clinical, cognitive and behavioral variability, making the identification of a single pattern of deficits and abilities a challenging task.